2023
DOI: 10.1186/s12870-023-04081-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of barley (Hordeum vulgare L.) under waterlogging stress, and overexpression of the HvADH4 gene confers waterlogging tolerance in transgenic Arabidopsis

Abstract: Background Waterlogging is one of the major abiotic stresses in barley and greatly reduces grain yield and quality. To explore the mechanism controlling waterlogging tolerance in barley, physiological, anatomical and transcriptional analyses were performed in two contrasting barley varieties, viz. Franklin (susceptible) and TX9425 (tolerant). Results Compared to Franklin, TX9425 had more adventitious roots and aerenchymas and higher antioxidant enz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
4
8
0
Order By: Relevance
“…The aerenchyma percentage increased significantly in both tested cultivars after one day of treatment, and it was further enhanced after three days of waterlogging, suggesting that this sampling window is suitable for the capture of gene expression changes associated with aerenchyma formation. Furthermore, while in general there is a relatively limited number of datasets representing barley root response to waterlogging, the time points between 1 and 3 d were also used by several recently published studies exploring response to waterlogging (Borrego-Benjumea et al, 2020; Luan et al, 2023). Using the same timepoints therefore may facilitate comparisons between gene expression response to waterlogging observed across several datasets, different experimental set ups and cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aerenchyma percentage increased significantly in both tested cultivars after one day of treatment, and it was further enhanced after three days of waterlogging, suggesting that this sampling window is suitable for the capture of gene expression changes associated with aerenchyma formation. Furthermore, while in general there is a relatively limited number of datasets representing barley root response to waterlogging, the time points between 1 and 3 d were also used by several recently published studies exploring response to waterlogging (Borrego-Benjumea et al, 2020; Luan et al, 2023). Using the same timepoints therefore may facilitate comparisons between gene expression response to waterlogging observed across several datasets, different experimental set ups and cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression changes observed at both time points, in both cultivars, highlighted GO terms associated with redox state management, metabolic adaptations and stress responses, suggesting that these processes play a key role in waterlogging response in barley (Figure 6). These GO terms have previously been linked to waterlogging responses in barley in other transcriptomic analyses (Borrego-Benjumea et al, 2020; Luan et al, 2023; Miricescu et al, 2023). In the first global transcriptomic study of barley root tissue under waterlogging stress, Borrego-Benjumea et al (2020) similarly identified enriched GO terms in the upregulated gene set for metabolism (carbohydrate, glycolytic and nucleoside), general enrichment for “oxidoreductase activity” and “response to chemical” related GO terms in Yerong root tissue subjected to 72 h waterlogging stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Transcriptome analysis in G. max after waterlogging stress showed a set of differentially expressed genes related to ET signaling, energy metabolism, and fermentation pathways [ 141 ]. During waterlogging stress in wheat plants, a transcriptome analysis was performed which showed a number of differentially expressed genes associated with oxidoreductase activity and biological response to ABA and SA [ 40 ].…”
Section: Strategies For Improving Waterlogging Tolerance In Plants: P...mentioning
confidence: 99%